2017
DOI: 10.15288/jsad.2017.78.249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations and Perceptions of Others’ Evaluations of Negative Alcohol-Related Consequences Predict Negative Alcohol-Related Consequences Among College Drinkers

Abstract: ABSTRACT. Objective: A key assumption when assessing alcoholrelated problems is that these problems are considered negative. A growing literature suggests that college drinkers do not perceive all measured consequences to be negative. Research has established the impact of others' beliefs on personal beliefs and behaviors. The purpose of this study was to assess the effect of perceptions of others' evaluations (POE) of consequences on one's own evaluations and subsequent experiences of consequences. Method: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Of these, three articles were from data collection efforts designed to measure HTO victimization among college students (Diep, Knibbe, Giang, & De Vries, 2015;Hallett et al, 2012;Langley, Kypri, & Stephenson, 2003). Of the 15 other studies, four included brief sections about HTO (i.e., Harvard's College Alcohol Survey, the Canadian Campus Survey, Ireland's College Lifestyle and Altitudinal Survey, and the Study to Prevent Alcohol-Related Consequences), two included brief sections about alcohol-related consequences in which a fewer than five HTO were included (Rinker, Young, Krieger, Lembo, & Neighbors, 2017;Strunin et al, 2014), and eight focused on a few specific HTO (Araas & Adams, 2008;Fair & Vanyur, 2011;Howard, Griffin, & Boekeloo, 2008;Neal & Fromme, 2007;O'Brien et al, 2017;Presley & Pimentel, 2006;Reed, Amaro, Matsumoto, & Kaysen, 2009;Wilhite, Mallard, & Fromme, 2018). As shown in Figure 2, this means most of the research studies on college HTO included fewer than five harms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, three articles were from data collection efforts designed to measure HTO victimization among college students (Diep, Knibbe, Giang, & De Vries, 2015;Hallett et al, 2012;Langley, Kypri, & Stephenson, 2003). Of the 15 other studies, four included brief sections about HTO (i.e., Harvard's College Alcohol Survey, the Canadian Campus Survey, Ireland's College Lifestyle and Altitudinal Survey, and the Study to Prevent Alcohol-Related Consequences), two included brief sections about alcohol-related consequences in which a fewer than five HTO were included (Rinker, Young, Krieger, Lembo, & Neighbors, 2017;Strunin et al, 2014), and eight focused on a few specific HTO (Araas & Adams, 2008;Fair & Vanyur, 2011;Howard, Griffin, & Boekeloo, 2008;Neal & Fromme, 2007;O'Brien et al, 2017;Presley & Pimentel, 2006;Reed, Amaro, Matsumoto, & Kaysen, 2009;Wilhite, Mallard, & Fromme, 2018). As shown in Figure 2, this means most of the research studies on college HTO included fewer than five harms.…”
Section: Resultsmentioning
confidence: 99%
“…Seven articles investigated associations between independent variables (e.g., drinking levels and protective behavioral strategies) and HTO (Abar, Mallett, Turrisi, & Abar, 2016;Araas & Adams, 2008;Cabalatungan & McCarthy, 2015;Nelson, Xuan, Lee, Weitzman, & Wechsler, 2009;Presley & Pimentel, 2006;Weitzman & Chen, 2005). One article used HTO to evaluate the A Matter of Degree program (Weitzman, Nelson, Lee, & Wechsler, 2004), and five included HTO as part of an investigation into alcohol-related harms (Adlaf, Demers, & Gliksman, 2015;Hope, 2011;Rinker et al, 2017;Strunin et al, 2014;Townshend, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The classroom example described has not been empirically assessed, whereas the alcohol example has been widely studied (e.g., Miller & Morrison, 2009; Prentice & Miller, 1993; Rinker et al, 2017; Schroeder & Prentice, 1998). These examples are simple to comprehend, provide clear cases of pluralistic ignorance, and have easily imaginable implications.…”
Section: Prototypical Examples Of Pluralistic Ignorancementioning
confidence: 99%
“…Pluralistic ignorance of alcohol use was consistently and extensively analyzed from 1993 (Prentice & Miller, 1993) to 2017 (Rinker et al, 2017), likely because of its pressing health implications among adolescents and young adults. Researchers found that individuals misperceive others as being more comfortable drinking alcohol, and in assessments of implications, found that (at least some) individuals conform to this misperceived majority (Prentice & Miller, 1993; Rinker et al, 2017; Segrist et al, 2007). Researchers also implemented interventions to reduce alcohol use and found that teaching individuals about pluralistic ignorance could reduce conformity (i.e., people drank less alcohol; Schroeder & Prentice, 1998).…”
Section: Pluralistic Ignorance Topics Assessedmentioning
confidence: 99%
See 1 more Smart Citation